Estimation of the utilities of attributes of intravenous iron infusion treatment for patients with iron-deficiency anemia: a conjoint analysis in Japan. (31st December 2023) - Takeshima, Tomomi; Ha, Chise; Iwasaki, Kosuke
Abstract: Aims: This study aimed to estimate the utility values of the factors associated with intravenous (IV) iron infusion treatment in Japanese patients with iron-deficiency anemia (IDA) from the patient's perspective. Methods: A conjoint analysis based on online survey data was conducted in May 2022 (registration number: UMIN000047756). Respondents in the main group were selected from the general population (20–69 years). Seven attributes were included in this analysis: waiting time before receiving an IV infusion, pain due to IV infusion, time required for IV infusion, number of IV infusions required to achieve treatment effect, frequency of hypophosphatemia as a side effect of IV infusion, frequency of skin discoloration by the drug solution, and out-of-pocket cost for one IV infusion visit. The utility of each level for each attribute was estimated using a logistic regression model as the difference from non-treatment. Results: The responses were collected from 1, 026 people. The utilities decreased with higher pain (−0.189 for pain level of 3.05), longer time for the IV infusion (−0.145 or −0.212 for 5 or 15 min), greater number of required IV infusions (−0.773 or −1.899 for 3 or 25 times), and higher frequency of adverse events (−0.373 or −0.385 for 13.0% or 14.2% of hypophosphatemia incidences; −0.502 for 2.3% of skin discoloration per one infusion). Limitations: Since this study was based on an online survey, the reliability of the results depends on whether the respondents understood the questions accurately. Further, the respondents were selected from an online panel, potentially affecting finding generalizability. Conclusions: The results indicate that utilities differ depending on the factors associated with IV iron infusion treatment. The findings of this study may be useful for informing future treatments or improving current treatment regimes, supporting the achievement of complete iron repletion for Japanese patients with IDA.